Pengaruh Upah Minimum Dan Pendidikan Terhadap Tingkat Partisipasi Angkatan Kerja Di Provinsi Sumatera Barat - Khairul Abrar; Nini Sumarni (Sharing: Journal of Islamic Economics Management and Business, 2026)
This study aims to analyze the influence of minimum wages and education levels on the Labor Force Participation Rate (TPAK) in West Sumatra Province. The study uses a quantitative method with an associative approach that focuses on the relationship between variables to test relevant theories. The data used are numerical data so that they can be analyzed statistically to determine the level of influence of each independent variable on the dependent variable. The research instrument was designed to measure the variables of minimum wages, education levels, and TPAK systematically and objectively. Data analysis techniques were carried out using inferential statistical methods to obtain accurate and accountable results. The results show that minimum wages have a significant influence on TPAK in West Sumatra. This is evidenced by a significance value of 0.001, which is smaller than the significance level of 0.05. Thus, an increase in the minimum wage contributes to changes in the community's labor force participation rate.